2020
DOI: 10.1002/pa.2131
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between carbon emission, financial development, and access to electricity: Incorporating the role of natural resources and population growth

Abstract: This study explores the nexus between financial development, access to electricity, and CO2 emissions in Pakistan over the period from 1990 to 2015, incorporating the role of natural resources and population growth. We checked the stationarity of the data by using three different unit root tests (ADF, Phillip Pesaran, and DG‐FLS). Long‐ and short‐run elasticities have been determined through auto‐regressive distributive lag (ARDL) method. The empirical results confirmed that financial development and access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Indeed, the growing level of CO2 emissions is corroborated with the findings (Asumadu- Sarkodie and Owusu, 2016, Shen et al 2020, Khan, Ju, Latif and Khan 2020, Saud, Chen and Haseeb, 2020.…”
Section: Dynamic Ardl Simulation Resultssupporting
confidence: 73%
“…Indeed, the growing level of CO2 emissions is corroborated with the findings (Asumadu- Sarkodie and Owusu, 2016, Shen et al 2020, Khan, Ju, Latif and Khan 2020, Saud, Chen and Haseeb, 2020.…”
Section: Dynamic Ardl Simulation Resultssupporting
confidence: 73%
“…Applying the ARDL, the study reported that in the long run, population density exerts a positive impact on emission. Khan et al (2020) incorporated the role of population growth and natural resources in exploring the association between electricity access, financial development and carbon emission in Pakistan. Utilizing data from 1990 to 2015 and the ARDL method, the paper reported among other things, that population growth accounts for the rising carbon emission in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, recent empirical studies on the impact of financial development on CO 2 emissions have presented mixed results. For example, Gill et al (2019), Gokmenoglu et al (2021), Nwani (2021), and Nwani and Omoke (2020) show that financial development reduces CO 2 emissions in Malaysia, Turkey, Venezuela, and Brazil, respectively, while Ibrahiem (2020), Iorember et al (2020), Khan et al (2021), and Shahbaz et al (2020) show it increases CO 2 emissions in Egypt, Nigeria, Pakistan, and the United Arab Emirates, respectively. Despite the growing interest on the topic, empirical evidence within the context of the Algeria economy is still scarce and lacking to the best of our knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%